Contribution of the Malpighian tubules for the maintenance of symbiotic microorganisms in cephalotes ants - Bution, M. L. [UNESP]; Caetano, Flávio Henrique [UNESP]; Zara, Fernando Jose [UNESP] (Pergamon-Elsevier B.V. Ltd, 2008)
Given the physiological importance of the Malpighian tubules to homeostasis in ants, this study aimed to characterize the enzymology, histology, histochemistry, and ultramorphology of the Malpighian tubules of Cephalotes atratus, C. clypeatus, and C. pusillus, as a contribution for the understanding of this organ, as well as to examine its role in the maintenance of symbiontic microorganisms in the ileum of these ants. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Malphigian tubules; Ants; Symbiotic microorganisms; Ileum